ANTI-INFLAMMATORY AND ANTI-OXIDANT ACTIVITIES OF METHANOL EXTRACT OF BAPHIA NITIDA - Chioma, Deborah Ejiogu (Universal Journal of Pharmaceutical Research, 2016)
Objectives: Baphia nitida is a tropical plant used in African folkloric medicine for the treatment of infections and inflammatory conditions. This study therefore seeks to investigate the biological activities including antioxidant and anti-inflammatory properties of leaf and root methanol extracts of B. nitida. Methods: Anti-inflammatory activity of extract was investigated by the carrageenan-induced paw edema model of inflammation, respectively. The antioxidant properties of the extracts as determined by the DPPH free radical scavenging assay. Results: The result showed that B. nitida extract caused a concentration dependent percentage increase of antioxidant activity. The leaves and root extract demonstrated potent anti-inflammatory activity at low concentrations of between 25-75 mg /kg body weight. The ascorbic acid standard had a better antioxidant activity of 63.59% at the concentration of 10 µg/ml and 81.63% at 400 µg/ml. Conclusion: The methanol root extract at lower doses exhibited anti-inflammatory properties. Methanol leaf extract than the root extract. Both the leaf and root extracts of B. nitida exhibited antioxidant activity. Peer Review History: Article received on- 10 October 2016; Revised on- 14 November; Accepted on- 13 December; Available online 15 January 2017 Academic Editor: Dr. Asia Selman Abdullah , Al-Razi university, Department of Pharmacy, Yemen, asia_abdullah65@yahoo.com Reviewer(s) detail: Dr. Xinwei Li , Jilin University, China, lixinwei100@jlu.edu.cn Prof. Dr. Ali Gamal Ahmed Al-kaf , Sana'a university, Yemen, alialkaf21@gmail.com